Explaining the safety of children's parks based on the physical components of the space (case study: parks in region 1 of Mashhad) - Behravesh, Hoda; Alizadeh, Katayoon; Jafari, Hamid (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Attention to the safety of children and adolescents as an effective stratum of society is inevitable. The stratum which the future of every city and country is in their hands. Nowadays, children in addition to nutrition, clean air and a shelter, need a safe and healthy open space to play and communicate with the environment. Flaws of urban spaces do not allow children to experiment and bring them to digital devices and solitaire games. The result is nothing but the growing individualist kids with a spirit of isolationism, a topic that can be called a threat to the health of the community. The present study is a small step towards recognizing the issues of the sense of security of children in the parks of Mashhad. In this research, the physical characteristics and space design, which include pass way quality indicators, lighting, urban furniture, and ultimately the security of space in parks of region 1 of Mashhad municipality will be analyzed. In this study, the research method is descriptive-analytical and with the understanding of effective physical indices on security through field, documentary and library studies, and comparing the contribution of these indices to other physical indices in similar samples, we explain the importance of these indices. Based on the data the most important physical factors affecting the improvement of security of children’s urban parks are the attention to the lighting index of all parks at nights, and also the reduction of out-of-sight locations and inducing fear in the design of the parks.